Integration of Sasaknese Traditional Game in Ethnoscience Learning: Preservice Teacher’s Perception - Soemardiawan Soemardiawan; Hilda Aqua Kusuma Wardhani; Agus Muliadi (Postgraduate, University of Mataram, 2023)
Study aims to explore the perceptions of prospective teacher students regarding the integration of traditional games in ethnoscience learning. This study is exploratory research conducted at the Mandalika University of Education with research subjects of 294 students. This research uses a research instrument in the form of a closed questionnaire with answers using a Likert scale and has been validated by experts. This research data was analyzed using quantitative descriptive statistics and inferential statistics with independent sample t-test. The results of this research are (1) the perceptions of prospective teacher students regarding the integration of traditional games in ethnoscience learning have an average score of 3.27 in the Very High category; (2) the perception of male prospective teacher students has an average score of 3.27 in the Very High category, while for women it is 3.29 in the Very High category; (3) there is no significant difference in the perceptions of male and female students regarding the integration of traditional games in ethnoscience learning, as evidenced by the significance value of 0.768 which is greater than 0.05 (>0.05).